2018
DOI: 10.1038/s41419-017-0072-x
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic apoptotic pathway activation increases response to anti-estrogens in luminal breast cancers

Abstract: Estrogen receptor-α positive (ERα+) breast cancer accounts for approximately 70–80% of the nearly 25,0000 new cases of breast cancer diagnosed in the US each year. Endocrine-targeted therapies (those that block ERα activity) serve as the first line of treatment in most cases. Despite the proven benefit of endocrine therapies, however, ERα+ breast tumors can develop resistance to endocrine therapy, causing disease progression or relapse, particularly in the metastatic setting. Anti-apoptotic Bcl-2 family protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…Senolytic drugs did not induce PARP cleavage in the untreated, proliferating Cal51 cells and had only a minimal effect on proliferating MDA-MB-175, consistent with no change or little change in cell number of proliferating cells treated with senolytic ( Fig. 1) and previous studies showing minimal activity of these drugs in solid tumor cell lines [44][45][46][47][48]. Treatment with appropriate senolytic drugs induced strong activation of caspase 3, as detected by immunofluorescence staining (Fig.…”
Section: Abt-263 Induces Apoptosis In Doxorubicin-induced Senescent Csupporting
confidence: 86%
See 1 more Smart Citation
“…Senolytic drugs did not induce PARP cleavage in the untreated, proliferating Cal51 cells and had only a minimal effect on proliferating MDA-MB-175, consistent with no change or little change in cell number of proliferating cells treated with senolytic ( Fig. 1) and previous studies showing minimal activity of these drugs in solid tumor cell lines [44][45][46][47][48]. Treatment with appropriate senolytic drugs induced strong activation of caspase 3, as detected by immunofluorescence staining (Fig.…”
Section: Abt-263 Induces Apoptosis In Doxorubicin-induced Senescent Csupporting
confidence: 86%
“…They include the BCL2 inhibitor , which is FDA approved for treatment of chronic lymphocytic leukemia [43], and ABT-263 (navitoclax), which inhibits BCL2, BCL-XL, and BCL-W and has activity in hematopoietic cancers [43]. Lamentably, these drugs have relatively minimal activity in solid tumors [44], including minimal or mixed responses as single agents in human breast cancer cell lines and xenografts [45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 There are three major subtypes of human breast cancer: endocrine-related/dependent breast cancer (estrogen receptor positive), 3 , 4 human epidermal growth factor receptor 2 (HER2)-positive breast cancer 5 7 and triple-negative breast cancer (TNBC) (estrogen receptor negative, progesterone receptor negative and HER2 negative). 8 , 9 While there are effective treatment strategies for endocrine-related/dependent breast cancer (tamoxifen and fulvestrant), 10 13 and antibody treatments (trastuzumab) 14 16 can effectively attenuate the progression of HER2-positive breast cancer, there is no effective therapeutic intervention for TNBC. Therefore, it is important to identify novel therapeutic molecular targets for TNBC treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, caspase-8 can truncate Bid into tBid to induce caspase signalling through mitochondrial dysfunction (Huang et al, 2016). Intracellular signals can stimulate mitochondria to induce mitochondrial swelling and increase mitochondrial membrane permeability, which causes the loss of mitochondrial transmembrane potential (ΔΨm) and the release of apoptogenic factors, including cytochrome c, Smac/Diablo, and AIF, followed by the activation of caspase-9 and caspase-3 (Williams et al, 2018). Intracellular signals can stimulate mitochondria to induce mitochondrial swelling and increase mitochondrial membrane permeability, which causes the loss of mitochondrial transmembrane potential (ΔΨm) and the release of apoptogenic factors, including cytochrome c, Smac/Diablo, and AIF, followed by the activation of caspase-9 and caspase-3 (Williams et al, 2018).…”
mentioning
confidence: 99%
“…Intracellular signals can stimulate mitochondria to induce mitochondrial swelling and increase mitochondrial membrane permeability, which causes the loss of mitochondrial transmembrane potential (ΔΨm) and the release of apoptogenic factors, including cytochrome c, Smac/Diablo, and AIF, followed by the activation of caspase-9 and caspase-3 (Williams et al, 2018). Moreover, recent reports showed that cellular reactive oxygen species (ROS) may mediate mitochondria-initiated apoptosis, because mitochondria are a primary target of ROS and a major endogenous source of ROS (Kim et al, 2017;Lin et al, 2016).…”
mentioning
confidence: 99%